2017
DOI: 10.1007/s13202-017-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Miocene Nukhul Formation (Gulf of Suez, Egypt): microfacies and reservoir characteristics

Abstract: The Lower Miocene Nukhul Formation was deposited during early stages of Gulf of Suez rifting. Outcrop of this formation at Gebel el Zeit, Egypt is up to 100 m (328 ft) in thickness and consists of lower sandstone-dominated and upper carbonate-dominated units. Samples were collected from the Nukhul Formation outcrop in order to describe the lithofacies, mineralogy, and petrographic characteristics to better understand the hydrocarbon reservoir potential of the unit. The investigations showed that the lower part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
(7 reference statements)
1
7
0
Order By: Relevance
“…The structural-tectonic framework of the southern Gulf of Suez (Figure 2(b)) was discussed recently by many authors (e.g. Patton et al 1994;Sharp et al 2000;Rohais et al 2016;Bosworth and Durocher 2017;Segev et al 2017;Temraz and Dypvik 2018).…”
Section: Geologic Settingmentioning
confidence: 80%
“…The structural-tectonic framework of the southern Gulf of Suez (Figure 2(b)) was discussed recently by many authors (e.g. Patton et al 1994;Sharp et al 2000;Rohais et al 2016;Bosworth and Durocher 2017;Segev et al 2017;Temraz and Dypvik 2018).…”
Section: Geologic Settingmentioning
confidence: 80%
“…The lower clastic interval of the Nukhul Formation deposited in shallow marine conditions (Schutz 1994;) and partially filling submarine gullies that transported debris from uplifted areas (Temraz and Dypvik 2018). However, some portions of Nukhul The Early Miocene Nukhul Formation is the first syn-rift rock unit in the in the Gulf of Suez area (Temraz and Dypvik 2018). Its type section located at Wadi Nukhul in the central eastern portion of the Gulf of Suez.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Its type section located at Wadi Nukhul in the central eastern portion of the Gulf of Suez. It is generally composed essentially of conglomerates, sandstones, shale and marl, limestones and evaporites Temraz and Dypvik 2018). In outcrops at the west of the Hurghada area, the lowermost syn-rift conglomerates referred as the Abu Gerfan Formation (Bosworth and McClay 2001).…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlumberger 1984;McClay et al 1998;McClay 2001. Sharp et al 2001;Young et al 2002;Jackson 2008;Khalil and McClay 2008;Hewaidy et al 2016;Pietrantonio et al 2016;Rohais et al 2016;Bosworth and Durocher 2017;Segev et al 2017;Temraz and Dypvik 2018) indicated that the stratigraphic section of the GOS basin can be divided into three major units of different thicknesses, depositional environments, areal distributions, and hydrocarbon potentialities. The inside of the GOS consists of Miocene and Post-Miocene rocks while outside the depression, the high relief ridges are built of basement rocks in the southern portion, followed to the north by Palaeozoic-Cenozoic sediments (Figure 1(c)).…”
Section: Geologic Settingsmentioning
confidence: 99%